A single-step one pot synthesis of dialkyl fluorophosphates from dialkylphosphites. Issue 31 (29th July 2015) - Purohit, Ajay Kumar; Pardasani, Deepak; Kumar, Ajeet; Goud, D. Raghavender; Jain, Rajiv; Dubey, D.K.
Graphical abstract: Abstract: An efficient synthetic method has been developed to obtain dialkyl fluorophosphates from dialkylphosphites using inorganic reagent (CuCl2 and CsF) at room temperature.